Branch‐Like Iron Nitride and Carbide Magnetic Fibres Using an Electrospinning Technique. Issue 19 (2nd March 2018) - García‐Márquez, Alfonso; Glatzel, Stefan; Kraupner, Alexander; Kiefer, Klaus; Siemensmeyer, Konrad; Giordano, Cristina
Abstract: Fe3 N and Fe3 C nanocomposites have a wide range of applications thanks to their ceramic nature, magnetic properties, conductivity and catalytic activity, just to cite some. In many fields optimal performances are ensured by crystallinity, homogeneity and hierarchical organization. In the present paper, crystalline, magnetic and well‐defined nanofibres of iron nitride and iron carbide/carbon nanocomposite with tunable composition and size were prepared via electrospinning. The starting polymeric material was directly electrospun into fibres and then calcined, leading to a highly homogeneous final product of nanoparticles along the fibres (both outside and inside). A mechanistic study was undertaken and here discussed. The magnetic properties of the as‐prepared nanofibres were also studied. The as‐prepared final fibre mat composite material can serve as active catalyst, for example, in oxygen reduction reaction (where nanofibres outperformed mere nanoparticles), it can serve as functional support for classical catalytic processes or, thanks to its magnetic properties, can be applied in magnetic‐field assisted separation or as magneto‐active membranes. Abstract : Electrospinning joins a sol‐gel process for the facile synthesis of ideal Fe3 N−Fe3 C/C magnetic fibres with full control over composition, size and crystallinity.